RESEPTIF DAN PRODUKTIF DALAM BAHASA ARAB - Miftachul Taubah; Ilzam Dhaifi (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Arabic language skills included in receptive abilities are listening skills and reading skills. Whereas, Arabic language skills which are included in are writing skills and speaking skills.